Estimation of Specific Storage and Transmissivity Coefficients for the Hamadan-Bahar Plain Aquifers Using the Stepwise- Balance Method - پگاه رئوفی منش; نجم الدین واصلی; محمودرضا شقاقیان (مهندسی منابع آب, 2015)
Specific Storage (Sy) and transmissivity (T) are two of the highly important hydrodynamic parameters required in estimation of the aquifer storage capacity and groundwater (GW) flow through the saturated zone to wells, qantas, springs, ** Water storage and water delivery coefficients in terms of studying aquifers for determining the best locations for drilling wells and exploitation of groundwater are highly important. Estimating these coefficients are usually conducted by the use of pumping tests, but mostly there are not enough wells appropriate for pumping tests or it is not practical to use pumping tests in all wells. Due to the limited number of exploration wells and lack of enough pumping tests and low accuracy of these tests in the under-study area of Dasht-e Bahar, there is no exact information reported about the hydrodynamic coefficients. Surface water resources are not in a good condition both qualitatively and quantitatively and thus groundwater is the main source of water supply in Bahar plain, Hamadan, Iran. For this reason have imposed increasing pressure on aquifers and irreparable damages. Thus, it is important to study the aquifer properties in Bahar plain including hydrodynamic coefficients. The purpose of this study, aquifer storage coefficient of Bahar plain,is calculated using stepwise balance method. Once a hydrodynamic coefficient is known in this method, other coefficients can be calculated. Still, in most cases, storage coefficient can be obtained once transmissivity coefficient is computed. The main precondition is the existence of two groundwater maps that are more accurate, one of which refers to the time of minimum balance (t) when water exchange through the aquifer level is insignificant and the other occurs with the Δt time difference. Same-level groundwater maps of June/July and August/September 2012 were used for Bahar plain, Hamadan. The average aquifer storage coefficient was computed using the above-mentioned method, which yielded a coefficient of 1.5, which seems a reasonable amount.